Detectability of Remanent Magnetism in the Crust of Venus. Issue 11 (5th June 2019) - O'Rourke, J. G.; Buz, J.; Fu, R. R.; Lillis, R. J.
Abstract: Observations of planetary magnetic fields provide fundamental insights into the origin and evolution of terrestrial planets. However, whether Venus ever hosted a dynamo is unknown. Here we show that crustal remanent magnetism is a potentially observable consequence of an ancient Venusian dynamo, in contrast to previous studies that dismissed this possibility. Past spacecraft measurements only exclude crustal magnetization near the Venera 4 landing site and northward of 50° South latitude for >150‐km coherence scales and strong magnetization intensities. Magnetite grains with sizes commonly observed in volcanic rocks can retain thermoremanent magnetism at Venusian conditions for >1 billion years. Depths to the Curie temperature of magnetite are ~5–40 km and typically less than predicted crustal thicknesses at our analyzed localities. Aerial platforms could detect expected magnetizations at horizontal scales similar to the ~50‐km operating altitude. Any detection would validate models of planetary accretion, geologic processes, and climate history. Plain Language Summary: Unlike Earth, Venus has no global magnetic field generated by churning fluid in its metallic core. Models indicate that Venus may have hosted an Earth‐strength field until at least a billion years ago—roughly the average surface age—if giant impacts mixed the core during planetary formation. Without energetic impacts, models suggest that chemical layering in the core would always suppress fluid motions and thus a dynamo. Searching for ancient magnetized rocks (already discovered on Moon, Mars, and Mercury) would test these models. Venus has a very hot surface, which decreases the stability of ancient magnetization and has caused pessimism about the chances of obtaining useful data. However, we found that common minerals such as magnetite are magnetically stable for billions of years at the current surface temperature. Enough crust could remain magnetized to produce signals detectable by orbiters at low altitudes or, ideally, aerial platforms floating in the atmosphere. Key Points: Whether Venus once hosted a dynamo‐generated magnetic field has broad implications for the accretion and evolution of terrestrial planets Despite high surface temperatures on Venus, magnetite and hematite grains may retain thermoremanent magnetization for >1 billion years Crust magnetized to depths of >1‐5 km could produce signals detectable by an aerial platform operating at ~50‐km altitude